The inquisitiveness mind set and the Qur’anic ethos: an exploration into Islamic inquisitiveness = Dasar pemikiran inkuisitif dan nilai-nilai etika dalam Quran: penerokaan ke dalam inkuisitif Islam - Badi, Jamal Ahmed Bashier; Machouche, Salah (IIUM Press, International Islamic University Malaysia, 2018)
gives with regards to fostering and nurturing the Inquisitive Mind set. The article will elaborate on the Qur’anic teachings on inquisitiveness. There are more than one thousand and two hundred questions in the Qur’an which are analysed to see their contribution to fostering inquisitive thinking. The multiple characteristics of the Inquisitive Mind set are explained by recourse to several prominent classical exegetists. The Qur’anic blue print for inquisitive learning is sketched briefly with an excursion into the etiquettes of inquisitiveness. A practical application of the theoretical discussion of inquisitiveness is provided in the context of recovering the Khaldūnian Legacy in sociology. The article concludes that fostering inquisitiveness is of the utmost importance, especially in our (post) modern times. It is hoped that the article will show, with innumerable evidence, that the Qur’an is a rich source for finding methods on developing an individual’s inquisitive mind set. ********************************************************* Etos Al-Qur'an menekankan peri pentingnya pemikiran atau perasaan ingin tahu. Tujuan kertas ini adalah untuk menunjukkan kedalaman maklumat teori dan nasihat praktikal yang disediakan oleh Alquran, dalam hal memupuk pemikiran ingin tahu. Artikel ini akan menghuraikan ajaran Al-Quran tentang pemikiran ingin tahu. Terdapat lebih dari seribu dua ratus soalan dalam Al-Qur'an, yang dianalisa dapat menyumbang kepada pemikiran ingin tahu. Ciri-ciri pemikiran ingin tahu telah dijelaskan oleh rekursi kepada beberapa eksegetis klasik yang terkenal. Pola pemikiran ingin tahu yang dijelaskan dalam Alquran digambarkan dengan penerokaan terhadap etika-etika pemikiran tersebut. Penggunaan praktikal teori pemikiran ingin tahu didapati dalam konteks pemulihan Warisan Khaldun dalam sosiologi. Artikel ini menyimpulkan bahawa memupuk perasaan ingin tahu adalah sangat penting, terutamanya pada zaman moden ini. Diharapkan artikel ini akan membuktikan bahawa Al-Qur'an adalah sumber yang kaya dengan kaedah-kaedah pembangunan pemikiran ingin tahu bagi seseorang individu.